Hybrid Rainfall Analysis in Semarang by Integrating SARIMA Predictions with Meteorological Association Rules - Agustin, Kristina; Novita Dewi, Ika (Politeknik Negeri Batam, 2026)
Climate variability necessitates advanced analytical approaches to understand irregular rainfall patterns, particularly in coastal cities like Semarang, Central Java. This research employs a dual-analysis framework combining the Seasonal Autoregressive Integrated Moving Average (SARIMA) model and the Apriori algorithm to forecast rainfall and uncover hidden meteorological associations. Analyzing BMKG monthly climatological data from January 2020 to December 2024, the research addresses both temporal trends and variable dependencies. The SARIMA 〖(1,0,0)(2,1,0)〗_12 model projected rainfall dynamics for 2025, identifying critical wet periods (January-March, November-December) and dry intervals (July-September), achieving a MAPE of 44.97%. To complement temporal forecasting, the Apriori algorithm was applied with 50% minimum support and 50% confidence, generating association rules from daily discretized meteorological data. Results reveal that the combination of low temperature (Tx_Low, Tn_Low) and moderate wind speed (FFx_Medium) exhibits the strongest correlation with heavy rainfall events Lift Ratio 12.34, indicating a 12-fold increased risk compared to random conditions. By synergizing temporal forecasting with the identification of meteorological triggers, this research offers a robust basis for early warning systems, supporting flood mitigation and water resource management strategies in Semarang.